Proteomic Analysis of Protein Ubiquitination Events in Dairy Goats with Fatty Liver - Yuli Zhu; Zhenhua Liu; Yuming Zhang; Yao Meng; Xunuo Song; Jinyu Li; Yue Zhang; Junkang Zhao; Liyin Du; Qinghua Deng (Animals, 2025)
Fatty liver is a major metabolic disease in periparturient dairy goats. Protein ubiquitination, a type of dynamic and multifaceted post-translational modification, plays an important role in metabolism by regulating the stability and function of target proteins. However, the hepatic protein ubiquitination profile in dairy goats with fatty liver is yet to be elucidated. In this study, we collected liver and blood samples from healthy dairy goats (Con, n = 3) and dairy goats with fatty liver (FL, n = 3). Then, we analyzed the overall ubiquitination of hepatic proteins in dairy goats with fatty liver through quantitative ubiquitin label-free proteomics and bioinformatics. Proteins showing significantly altered levels of ubiquitination were identified via bioinformatics, and related regulatory pathways were screened. The results showed that the blood levels of beta-hydroxybutyric acid and non-esterified fatty acids were significantly upregulated in dairy goats with fatty liver, and a total of 238 ubiquitination sites across 921 proteins were found to be differentially altered in the fatty liver group. Among them, ubiquitination was upregulated at 351 sites across 93 proteins and downregulated at 570 sites across 145 proteins. In addition, GO and KEGG pathway analysis revealed that the differentially ubiquitinated proteins were enriched in pathways regulating lipid metabolism, such as the PPAR signaling pathway, fatty acid degradation, and peroxisome activity. Notably, by observing the overlap among these three sub-networks, we found that proteins with downregulated ubiquitination—such as ACSL1, ACSL5, EHHADH, and ACAA1—were transcriptionally upregulated in dairy goats with fatty liver. This study reveals the key ubiquitinated proteins in dairy goats with fatty liver and provides a more comprehensive understanding of the pathogenesis of fatty liver in dairy goats.